Bound Putrescine, a Distinctive Player under Salt Stress in the Natrophilic Sugar Beet in Contrast to Glycophyte Tobacco - R Hajiboland (Journal of Sciences, Islamic Republic of Iran)
The influence of salinity on the different polyamine fractions (free, conjugated, and bound) was compared in a natrophilic halophyte (Beta vulgaris L. cv. IC) and a salt sensitive glycophyte (Nicotiana rustica L. cv. Basmas). Low-level salinity (25 mM NaCl) and high salinity (150 and 50 mM NaCl for sugar beet and tobacco, respectively) were supplied in hydroponics. Under low salinity shoot dry weight increased in sugar beet, but decreased in tobacco. Under high salinity growth reduction in sugar beet and tobacco were similar. However, sugar beet accumulated higher Na and Cl in roots and shoots than tobacco. Low salinity caused an increase (22%) in the rate of net CO2 assimilation in sugar beet. This parameter was depressed in both species under high salinity. Sugar beet had constitutively higher free spermine levels in roots and shoots than tobacco. Spermidine levels were constitutively higher in shoots of sugar beet and in roots of tobacco. Under salt stress tobacco plants tended to increase free polyamine levels. The most important salt–induced rise in polyamine titer, however, was found in roots and shoots of sugar beet. In sugar beet roots the bound putrescine fraction increased 9.3-fold under growth- stimulating salt supply (25mM) and 20-fold under salt stress (150 mM). In tobacco roots this fraction only increased 2.3 and 3.8-fold under mild (25 mM) and high salt stress (50 mM), respectively. Our results provide support to the view that bound putrescine contributes to the protection against salt stress in the natrophilic sugar beet.